PATHOPHYSIOLOGICAL MECHANISMS AND CLINICAL SIGNIFICANCE OF HYPOTHYROIDISM - Sharofiddinov Javlon Komoliddinovich,; Ikromova Dilnura Dilmurodovna, (TADQIQOTLAR, 2026)
Abstract: Hypothyroidism is a common endocrine disorder characterized by a deficiency  of  thyroid  hormones.  According  to  current  data,  overt  hypothyroidism occurs  in  approximately  0.3–5%  of  the  general  population,  while  subclinical hypothyroidism is found in about 4–10%, reaching up to 12% in some populations. It is  observed  more  frequently  among  women  and  elderly  individuals.This  condition affects the body by disrupting metabolism, cardiovascular function, nervous system activity,  digestive  processes,  and  reproductive  function.  Hypothyroidism  often develops slowly and insidiously, which may delay its early diagnosis. If not identified and treated in time, it can lead to serious complications such as myxedema, infertility, atherosclerosis,  heart  failure,  and  cognitive  impairment.  Therefore,  studying  the pathophysiological mechanisms and clinical significance of hypothyroidism is of great importance in modern medicine.